Analysis of Student Learning Difficulties on Class VIII Plant Structure and Function Material at Mts Wahid Hasyim 02 Dau - Maria Elvi; Zuni Mitasari; Anis Samrotul Lathifah (Universitas Veteran Bangun Nusantara Sukoharjo, 2022)
This study aims to determine the level of difficulty of student learning on the structure and function of plants and what factors cause it. The method used in this study is quantitative descriptive method. The data collection techniques used were observation, written tests and questionnaires. The results showed that the level of student learning difficulty in plant structure and function material was in the high category and the causative factor was from the school environment with a percentage of 33.4% (high). The factor causing students' learning difficulties in the structure and function of class VIII plants at MTs Wahid Hasyim 02 Dau is caused by school environmental factors with high influence categories.